Molecular detection and characterization of begomoviruses from Burkina Faso and Nicaragua - Rachapudi, Suneel Sekhar (2019)
Agriculture plays a major role in the economy of countries in Africa and America. Viruses have emerged as major plant pathogens during the last few decades on agriculturally important field crop plants. The genus Begomovirus belongs to the family Geminiviridae, which is the largest family of plant-infecting viruses. Geminiviruses can infect both monocot and dicot plants. Begomoviruses have circular, single-stranded DNA (css-DNA) genomes with one or two equally sized genome components (~2.7 kb each). In previous studies, the begomoviruses, tomato leaf curl Mali virus (ToLCMLV), tomato yellow leaf curl Mali virus (ToYLCMV) and pepper yellow vein Mali virus (PeYVMLV) were found in tomato (Solanum lycopersicum) plants from Burkina Faso, while bean golden yellow mosaic virus (BGYMV) and calopogonium golden mosaic virus (CalGMV) had been found in common bean (Phaseolus vulgaris) plants from Nicaragua.